The Relationship Between Physical Activity and Balance Control in the Elderly - Mohammad Taghipour; Seyed Reza Hosseini; Salma Pouraria (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: Aging is a process which causes some changes in physical, psychological, and social aspects of human body. These changes result in decrease in the quality of life and independency. Senility is an important part of the human society and the established changes in the elderly influence his or her relatives and the whole society. Regarding the importance of this topic and a few studies in this field, the purpos of the study is to study the physical activity, the balance control, and their relationship in the elderly. Methods & Materials: In this cross-sectional study, 1614 old people living in Amir Kola City, Iran participated. The research conducted between 2012 and 2013. Their physical activity was measured using standard questionnaire of the physical activity of PASE (the physical activity scale for the elderly), their balance control by Berg Balance test. Then, the data were analyzed through the Chi-square and t test using SPSS. P values less than 0.05 were considered significant. Results: A total of 1614 the elderly people were analyzed in this study (883 males and 733 females). The mean (SD) age of men was 69.96(7.68) and for women it was 68.66(7.02). The relationship between the degree of physical activity and balance control in studied people was statistically significant and direct (P=0.000). Conclusion: The results of this study indicate the existence of significant relation between balance control and physical activity in the elderly. The result also suggests that it is possible to improve the balance control in the elderly by planning to increase the physical activity among them and decrease the related problems such as falling.